Methods for acoustic sounding of the atmosphere using antenna arrays - Kartashov, V.M.; Bobnev, R.O. (Radiotekhnika, 2025)
Acoustic sounding systems (AS) of the atmosphere – sodars provide information on the state of processes occurring in the lower layers of the atmosphere. They allow measuring vertical profiles of wind speed and direction, turbulence parameters. The information obtained is used in applied tasks to ensure takeoff and landing of aircraft, study of atmospheric processes. However, the effectiveness of existing acoustic means is insufficient and there are practical needs for the development of appropriate promising methods of sounding and signal processing, which will be implemented when building specific stations. The recent development of effective piezoelectric acoustic emitters has provided the possibility of creating acoustic antennas for sodars in the form of antenna arrays, which has had a significant impact on the structure of the acoustic locator and allows expanding significantly its potential capabilities. However, the use of acoustic antenna arrays in sodars has a number of features, so it is necessary to conduct additional research to analyze the potential capabilities of emerging sodars. The article considers methods for remote sensing of the atmosphere by sodars with an antenna array when performing simultaneous sensing in several directions. Adequate mathematical models of acoustic signals and methods of multi-channel sensing have been developed, mathematical computer modeling of sensing processes has been performed. The proposed method has been analyzed when performing simultaneous sensing of the atmosphere in several directions at one frequency, as well as when using different frequencies of sensing signals in different directions. The implementation of the considered methods in practice will ensure increased efficiency and reduced time for measuring atmospheric characteristics. Mathematical modeling of methods for adaptive spatial selectivity of acoustic locators with an adaptive antenna array has been performed, their significant potential capabilities have been shown. The implementation of such methods in practice will allow increasing significantly the noise immunity of acoustic locators, especially when they operate in difficult interference conditions, for example, in airport conditions.